Off-peak frequency in regional public transport - Hansson, Joel (Lund University, 2021)
The purpose of this study is to look into patronage effects of extended supply outside peak hours on regional public transport services. The patronage effects are explored through four case studies from the region of Scania (Skåne), south Sweden. The cases include rail, coach, and bus services where substantial improvements have been made outside peak hours, resulting in at least hourly all-day services. Two datasets are used: one with panel data, covering 10-14 years of annual measurements of the daily number of trips, and one with before-and-after data where the number of trips on individual departures have been recorded at two points in time.

Trip data in the form of daily passenger numbers (weekdays, Saturdays, Sundays), annual observations. Panel data comprising four different public transport services over 10-14 years. Besides the trip data, the dataset also includes the number of daily departures, ticket prices, petrol prices, and population data.

Syftet med studien är att undersöka effekter på resandet av utökat turutbud utanför rusningstid i regional kollektivtrafik. Resandeeffekterna utforskas genom fyra fallstudier i Skåne. Fallstudierna inkluderar regionala tåg- och busslinjer där substantiella förbättringar gjorts av turutbudet utanför rusningstid, vilket resulterat i åtminstone timmestrafik hela dagen. Två uppsättningar data används: en med paneldata som spänner över 10-14 års årliga mätningar av antal resor per dag, och en med före-och-efter-mätningar där antal resor på enskilda avgångar har noterats vid två olika tidpunkter.

Resandestatistik i form av antal resor per dag (vardag, lördag, söndag) i årliga observationer. Paneldata som omfattar fyra olika kollektivtrafiklinjer under 10-14 år. Förutom resandestatistiken ingår även antal avgångar, prisuppgifter för kollektivtrafikresorna, bensinpris och befolkningsstatistik.
Turutbud utanför rusningstid i regional kollektivtrafik
Keywords: public transport; allmänna kommunikationer; rural area; lantligt område; Transport networks; Transportnät; Utility and governmental services; Allmännyttiga och offentliga tjänster; accessibility; tillgänglighet; timetables; tidtabeller; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Transport Systems and Logistics; Transportteknik och logistik; Transportation; Transporter